Preparation method of slow-release material, prepared slow-release material and application thereof

CN120024986BActive Publication Date: 2026-11-03CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311552994.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-21
Publication Date
2026-11-03
Estimated Expiration
2043-11-21

AI Technical Summary

Technical Problem

Existing slow-release materials have problems when remediating organic pollutants in soil and groundwater, such as unsuitable matrix materials for long-term release and short release cycles, which prevent them from achieving long-term remediation.

Method used

By using a modified porous starch and activated carbon composite material, a multi-layer encapsulation structure is formed through a sequential batch mixing method. Combined with a specific material ratio, a graded release slow-release material is prepared for the remediation of organic pollutants in soil and groundwater.

Benefits of technology

It achieves long-term and efficient pollutant remediation, extends the agent release cycle, improves pollutant removal efficiency, reduces agent dosage, prevents pollution rebound, and does not cause secondary pollution of groundwater.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120024986B_ABST
    Figure CN120024986B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a slow-release material, the slow-release material prepared by the method and application of the slow-release material. The method comprises the following steps: (1) dispersing first starch in water, then adding a first active substance, activated carbon and sodium alginate and uniformly mixing to obtain product I; (2) dispersing second starch in water, then adding a second active substance and uniformly mixing to obtain product II; (3) mixing product I obtained in the step (1), product II obtained in the step (2), a strength agent, a matrix and a solvent, shaping, drying and obtaining the slow-release material; wherein the first starch in the step (1) and / or the first starch in the step (2) is modified porous starch. The slow-release material prepared by the method has the characteristics of environmental friendliness and long-term release, can be used in the slow-release release aspect of the slow-release material, and can achieve long-term and efficient repair when being used for repairing soil and underground water organic pollutants.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of sustained-release materials technology, specifically relating to a method for preparing sustained-release materials, the prepared sustained-release materials, and their applications. Background Technology

[0002] As the battle to protect clean soil continues, the remediation of contaminants in soil and groundwater has increasingly attracted researchers' attention. Organic pollutants present in industrial sites, such as trichloroethylene (TCE), tetrachloroethylene (PCE), and petroleum hydrocarbons, can severely damage ecosystems and pose significant harm to humans and animals. Furthermore, these pollutants are difficult to degrade naturally, making artificial remediation essential. In-situ chemical oxidation (ISCO) is one of the most commonly used remediation technologies for groundwater remediation due to its high remediation efficiency and minimal impact on contaminated sites.

[0003] While chemical oxidation remediation is highly efficient, the oxidant cannot remain underground for extended periods, necessitating continuous addition of reagents. This increases remediation costs and exacerbates secondary pollution. Therefore, there is a need to develop methods that enable long-term remediation to achieve effective and stable results. Slow-release materials, which extend the release time of reactants through a lower release rate, are increasingly being applied to groundwater remediation due to their potential to achieve long-term effectiveness.

[0004] CN102491425A discloses a slow-release potassium permanganate oxidant for in-situ chemical remediation of groundwater. This study disperses KMnO4 into molten paraffin wax, then cools and solidifies it in a mold to produce slow-release KMnO4 oxidants of various shapes, thereby achieving the purpose of slow-release KMnO4 oxidant. However, this study uses harmful organic paraffin wax as one of the raw materials, posing a significant risk of secondary pollution.

[0005] CN107188361A discloses a slow-release sulfiding agent, its preparation method, and a method for using the slow-release sulfiding agent to purify heavy metals and arsenic in acidic solutions. This research is conducted on Fe-containing... 2+ Mn 2+ and Zn 2+ A slow-release sulfiding agent, a nano- to micron-sized metal sulfide sol, is obtained by reacting a sulfur source and surfactant in a solution. This agent is used to remove heavy metals and arsenic from acidic solutions, exhibiting advantages such as high removal efficiency, low sulfiding agent usage, and low hydrogen sulfide release. However, this agent is only effective against heavy metal pollutants and cannot remediate organically contaminated groundwater, and it is difficult to achieve long-term remediation.

[0006] CN114160558A discloses an in-situ chemical barrier material for contaminated soil, its preparation, and its application. The material uses clean soil from the site or soil meeting landfill disposal standards as the main matrix material, while adding clay minerals to significantly reduce the permeability coefficient of the barrier mixture. Furthermore, the application of active materials in the mixture effectively controls and assists in the reduction of pollutants, thereby achieving the goals of in-situ risk management and remediation of contaminated sites through multiple functional characteristics. However, this material uses soil as the main matrix material. Experimental data shows that soil and clay, as matrix materials, readily absorb water, swell, and disintegrate upon contact with water, greatly reducing the release time of the active components in the material and failing to achieve the purpose of slow release and long-term remediation.

[0007] In summary, existing slow-release remediation materials and methods are either only suitable for heavy metal contaminated sites and have limited effectiveness in remediating organic pollutants, or their matrix materials are unsuitable for long-term release and have short release cycles, thus failing to achieve the goal of slow release and long-term remediation. Therefore, there is an urgent need to develop an environmentally friendly, long-term release slow-release material. Summary of the Invention

[0008] To address the shortcomings of existing technologies, this invention provides a method for preparing a sustained-release material, the prepared sustained-release material, and its applications. The sustained-release material prepared by this method is environmentally friendly and has long-term release characteristics, making it suitable for the sustained-release of materials, particularly for the long-term and efficient remediation of organic pollutants in soil and groundwater.

[0009] The first aspect of this invention provides a method for preparing a sustained-release material. The method includes:

[0010] (1) Disperse the first starch in water, then add the first active substance, activated carbon, and sodium alginate and mix evenly to obtain product I;

[0011] (2) Disperse the second starch in water, then add the second active substance and mix well to obtain product II;

[0012] (3) Mix product I obtained in step (1), product II obtained in step (2), strength agent, matrix and solvent, mold and dry to obtain sustained-release material.

[0013] According to the present invention, the first starch in step (1) and / or the second starch in step (2) are modified porous starches. The first starch in step (1) and the second starch in step (2) can be the same starch or different starches.

[0014] According to the present invention, the method for preparing the modified porous starch includes:

[0015] Porous starch was dispersed in water, and octenyl succinic anhydride was added to carry out the reaction. The solid was filtered and dried to obtain modified porous starch.

[0016] According to the present invention, in the method for preparing the modified porous starch, the porous starch is dispersed in water to obtain an emulsion, and the mass content of the porous starch is 25wt% to 40wt%.

[0017] According to the present invention, in the preparation method of the modified porous starch, the mass ratio of octenyl succinic anhydride to porous starch is 1:(30-55).

[0018] According to the present invention, in the method for preparing the modified porous starch, the reaction conditions are as follows: reaction temperature of 40–55°C, pH of the reaction solution controlled at 8.5–10.5, and reaction time of 2–6 h. Further, the reaction is terminated by adjusting the pH of the reaction solution to below 6. After termination of the reaction, the product is washed, filtered, and dried. The drying conditions are as follows: temperature of 45–55°C, and time of 10–16 h.

[0019] According to the present invention, in the preparation method of the modified porous starch, the porous starch can be commercially available or homemade. The median pore size of the porous starch is 4.5–6.5 μm. The modified porous starch possesses both hydrophilic and ester-philic properties. After adsorption and binding with activated carbon, it can both facilitate the strong binding of activated carbon and inorganic oxidants and enhance the hydrophilicity of the activated carbon itself, promoting the entry of polluted water into the pores and aiding in the efficient degradation of pollutants.

[0020] According to the present invention, preferably, the porous starch can be prepared using conventional methods. Further, the method for preparing the porous starch includes: adding α-amylase and saccharifying enzyme to a starch-water suspension, reacting, filtering, and drying the resulting residue to obtain porous starch.

[0021] According to the present invention, in the method for preparing porous starch, the starch includes one or more of corn starch, potato starch, and cassava starch.

[0022] According to the present invention, in the method for preparing porous starch, the starch content in the suspension is 15wt% to 30wt%.

[0023] According to the present invention, in the method for preparing porous starch, the pH value of the suspension is 4.5 to 6.5.

[0024] According to the present invention, in the method for preparing porous starch, the suspension is preheated before adding α-amylase and saccharifying enzyme. The preheating temperature is 25-30°C, and the preheating time is 20-30 minutes.

[0025] According to the present invention, in the method for preparing porous starch, the reaction conditions are: temperature 30-40°C, time 33-35 minutes.

[0026] According to the present invention, in the method for preparing porous starch, the mass ratio of α-amylase to saccharifying enzyme is 1:(3.5-5.5).

[0027] According to the present invention, in the method for preparing porous starch, the total amount of α-amylase and saccharifying enzyme added accounts for 0.03‰ to 0.11‰ of the mass of the suspension.

[0028] According to the present invention, in the method for preparing porous starch, the drying conditions are: drying at 45-55°C for 16-24 hours.

[0029] According to the present invention, the first active substance in step (1) includes one or more of sodium persulfate, potassium persulfate, ammonium persulfate, calcium persulfate, potassium permanganate, sodium permanganate, sodium sulfite, and microbial nutrients, preferably one or more of sodium persulfate, potassium persulfate, and ammonium persulfate. Further, the microbial nutrient includes at least one of glucose, lignin, nitrate, and ferrous salt. The first active substance does not produce harmful substances or cause secondary pollution of groundwater after oxidation-reduction or biological utilization.

[0030] According to the present invention, the activated carbon in step (1) has a particle diameter of 40-60 mesh. The activated carbon is wood-based activated carbon and / or coal-based activated carbon. In the activated carbon, macropores (pore size > 50 nm) account for more than 5% of the total pore volume, preferably 5%-8%.

[0031] According to the present invention, in step (1), the materials are fed in the following ratio: water, sodium alginate, first starch, first active substance, and activated carbon at a mass ratio of 100:(1-3):(5-15):(35-50):(30-45). The product prepared within this ratio range can maximize the loading of the first starch particles carrying the first active substance into the pores of the activated carbon.

[0032] According to the present invention, in step (1), after dispersing the first starch in water, it should be stirred thoroughly. Then, the first active substance, activated carbon, and finally sodium alginate are added in sequence. Each time a material is added, it should be mixed evenly. Preferably, stirring should be performed after adding activated carbon, preferably mechanical stirring. The mechanical stirring device can be a magnetic stirrer. Preferably, the mechanical stirring time is 1 to 2.5 hours. More preferably, sodium alginate is added during the stirring process.

[0033] According to the present invention, in step (1), product I is shaken in a shaker. The shaking time is 30-50 min, so that the starch carrying the active substance is fully loaded into the activated carbon. The resulting product I is an activated carbon composite material loaded with the first active substance.

[0034] According to the present invention, product I in step (1) can be filtered, washed and dried. The drying can be natural drying, for example, drying at room temperature (10-25°C) for 10-48 hours.

[0035] According to the present invention, the second active substance in step (2) includes one or more of sodium persulfate, potassium persulfate, ammonium persulfate, calcium persulfate, potassium permanganate, sodium permanganate, sodium sulfite, and microbial nutrients, preferably one or more of sodium persulfate, potassium persulfate, and ammonium persulfate. Further, the microbial nutrient includes at least one of glucose, lignin, nitrate, and ferrous salt. The second active substance does not produce harmful substances or cause secondary pollution of groundwater after oxidation-reduction or biological utilization. The first and second active substances can be the same or different.

[0036] According to the present invention, the mass ratio of water, second starch and second active substance in step (2) is 100:(20-30):(50-60).

[0037] According to the present invention, the strength agent in step (3) includes at least one of quartz sand and glass fiber. The strength agent provides mechanical strength to the sustained-release material and simultaneously creates large pores, increasing the drug release rate. The matrix includes one or more of polytetrafluoroethylene (PTFE), polystyrene (PS), polyethylene (PE), and polypropylene (PP). The matrix serves as the matrix skeleton material of the sustained-release material, providing support and bonding. The solvent includes at least one of dichloromethane and n-hexane. Preferably, the solvent includes dichloromethane and n-hexane. Preferably, the volume ratio of dichloromethane to n-hexane is 1:(0.5-1). The solvent evaporates and dissipates after the material is formed and is not present in the material.

[0038] According to the present invention, in step (3), the mass ratio of product I, product II, strength agent, matrix, and solvent is (80-95):(75-85):(1-3):100:(50-70). This feeding ratio allows it to form a layered encapsulated structure, with the matrix material encapsulating the second active substance as the outer shell and the activated carbon composite material loaded with the first active substance as the inner core. In sustained-release applications, this further creates a staged release effect, prolonging the drug release time and increasing the oxidation cycle.

[0039] According to the present invention, preferably, in step (3), the mixing method of product I, product II, strength agent, matrix, and solvent includes:

[0040] (31) Mix the matrix with the solvent;

[0041] (32) The mixture obtained in step (31) is mixed evenly with product I;

[0042] (33) Mix the mixture obtained in step (32), product II and strength agent evenly.

[0043] According to the present invention, the slow-release material in step (3) has a shape including at least one of cylindrical, spherical, strip-shaped and tablet-shaped.

[0044] According to the present invention, the drying conditions in step (3) are: temperature 30-45°C and time 30-60 hours.

[0045] A second aspect of the present invention provides a sustained-release material prepared by the above method.

[0046] A third aspect of the present invention provides an application of the sustained-release material prepared by the above method in the field of sustained release.

[0047] According to the present invention, the application includes the use of slow-release materials in the remediation of organic pollutants in groundwater.

[0048] According to the present invention, the application involves using the aforementioned slow-release material as a filler, filling it into permeable reactive barriers, groundwater remediation wells, and other remediation structures to carry out in-situ chemical oxidation, in-situ chemical reduction, and in-situ bioremediation of contaminated groundwater. During the in-situ chemical oxidation and reduction processes, when groundwater carrying pollutants flows through the filler, it undergoes oxidation-reduction reactions with the active substances released by the slow-release material, resulting in the removal of pollutants and purification of the groundwater. During the in-situ bioremediation process, the carbon source, nitrogen source, electron acceptor, and other nutrients released by the slow-release material prepared by the above method provide sustained support for microbial agents, thereby accelerating the degradation of pollutants by microorganisms and achieving groundwater remediation.

[0049] Compared with the prior art, the present invention has achieved significant and outstanding technical effects:

[0050] (1) In the method of the present invention, the method adopts a sequential batch mixing method to form a multi-core structure of the sustained-release material with multiple layers. After the outer shell is decomposed, multiple dispersed cores in the inner layer can release the active substance from the inner layer to the outer layer in turn, achieving the effect of multi-level release in layers, thereby realizing the long-term stable drug release.

[0051] Furthermore, in the method, starch is modified with octenyl succinic anhydride to give it both hydrophilic and ester-philic properties. When combined with activated carbon adsorption, it can not only help activated carbon to firmly bind with inorganic oxidants, but also improve the hydrophilicity of activated carbon itself to promote the entry of polluted water into the pores, thus improving the contact efficiency of pollutants and slow-release materials.

[0052] (2) The unique material ratio scheme in the product of this invention ensures the loading of active substances while achieving close integration of active substances with other materials, develops a high-strength skeleton structure, avoids material breakage and disintegration in water, and prolongs the grading speed of finished material in water.

[0053] (3) The slow-release material prepared by the method of the present invention can effectively prolong the release cycle of the agent and stabilize the release rate. In particular, when applied to the remediation of pollutants in groundwater, it can improve the removal efficiency of pollutants and the stability of technical operation, reduce the amount of agent added, and prevent pollution rebound. Attached Figure Description

[0054] Figure 1 This is a graph showing the sustained-release performance test results of Example 1;

[0055] Figure 2 This is a graph showing the sustained-release performance test results of Example 2;

[0056] Figure 3 This is a graph showing the sustained-release performance test results of Example 3;

[0057] Figure 4 The graph shows the sustained-release performance test results of Comparative Example 1;

[0058] Figure 5 A simplified diagram of a contaminated groundwater treatment device for an application example;

[0059] Figure 6 The image shows the effect of slow-release materials on the remediation of petroleum hydrocarbon (TPH) contaminated groundwater as an application example. Detailed Implementation

[0060] The present invention will be further illustrated by the following embodiments, but the scope of protection of the present invention is not limited by the embodiments.

[0061] In this invention, the method for testing the sustained-release performance is as follows: 10g of the sustained-release material is placed in 1L of deionized water. The content of active substances in the water is measured at regular intervals, and the level of organic matter in the water is also measured simultaneously to detect whether the sustained-release material will cause secondary pollution of the water body. The testing interval increases with the testing time. For example, in the initial stage, it can be every 1 day; in the middle stage, it can be every 2-5 days; and in the final stage, it can be every 10 days. After each test, the deionized water used for testing is replaced with 1L of fresh deionized water. The above steps are repeated periodically until no active substances can be detected in the deionized water. In this invention, the content of active substances in the water is tested using spectrophotometry. For example, when persulfate is used as the active substance, the persulfate content is tested using the potassium iodide-ultraviolet spectrophotometric method. When ferrous salt is used as the active substance, the iron content is tested using the o-phenanthroline spectrophotometric method. When glucose is used as the active substance, the glucose content is determined by high-performance liquid chromatography.

[0062] In this invention, the method for testing organic matter in water is the method specified in "Determination of Volatile Organic Compounds in Water by Purge-Trap-Gas Chromatography (HJ 686-2014)".

[0063] In this invention, the loading of active substances in the prepared sustained-release materials was determined using an elemental analyzer. In this invention, the release period is the time from when the sustained-release material is added to water until the active substance is no longer detectable in the water; the cumulative release rate of the sustained-release material is the sum of the masses of active substances measured each time within the release period, divided by the loading of active substances in the sustained-release material; the average release rate is the sum of the masses of active substances measured each time within the release period, divided by the release period.

[0064] Example 1

[0065] (1) The preparation method of modified porous starch is as follows:

[0066] Preparation of porous starch: Corn starch was added to water and stirred until homogeneous to prepare a 30 wt% starch suspension with a pH of 5.5. The suspension was preheated in a water bath at 30°C for 30 minutes. Then, a mixture of α-amylase and saccharifying enzyme at a mass ratio of 1:5.5 was added to the starch suspension, with the total amount of α-amylase and saccharifying enzyme being 0.11‰ of the suspension mass. The suspension was kept at a constant temperature of 40°C in a water bath for 33 minutes. After filtration to remove water, the mixture was dried in a 45°C oven for 24 hours to obtain porous starch. The median pore size of the porous starch was 6.5 μm.

[0067] Preparation of modified porous starch: Using the porous starch prepared above as raw material, water was added to make a 40 wt% starch emulsion. Octenyl succinic anhydride was added, with a mass ratio of octenyl succinic anhydride to porous starch in the starch emulsion of 1:55. The reaction was maintained at a constant temperature of 55℃ in a water bath for 3 hours, and the pH of the reaction solution was controlled at 9. Then, hydrochloric acid was added to adjust the pH to 6 to end the reaction. The reaction product was washed, filtered, and dried at 50℃ for 13 hours to obtain modified porous starch.

[0068] In this example, both the first and second starches are modified porous starches as described above.

[0069] 15g of starch was added to 100g of water and stirred thoroughly to form an emulsion. Then, 50g of sodium persulfate was added to the emulsion and dissolved and mixed. After stirring evenly, 45g of 60-mesh wood-based activated carbon (with macropores accounting for 5.3% of the total pore volume) was added to the mixture. The mixture was then stirred thoroughly in a magnetic stirrer for 2 hours. Then, while stirring, 3g of sodium alginate was added to form a colloid. The colloid was placed in a shaker and shaken for 45 minutes to allow the starch containing active substances to be fully loaded into the activated carbon. The adsorbed activated carbon was then filtered, washed, and air-dried at 25°C for 48 hours to obtain product I, i.e., the activated carbon composite material.

[0070] (2) Weigh some of the above-mentioned modified porous starch again as the second starch, and sodium persulfate. Mix the starch and sodium persulfate in water to obtain product II. The mass ratio of the feed is water:starch:sodium persulfate = 100:30:60.

[0071] (3) Mix product I obtained in step (1), product II obtained in step (2), strength agent, matrix, and solvent, and then mold and dry to obtain a sustained-release material. The specific steps are as follows:

[0072] (31) Mix the matrix polytetrafluoroethylene powder with a solvent (dichloromethane and n-hexane in a volume ratio of 1:1);

[0073] (32) The mixture obtained in step (31) is mixed evenly with product I;

[0074] (33) The mixture obtained in step (32), product II, and the strength agent quartz sand are thoroughly mixed. The product I: product II: quartz sand: polytetrafluoroethylene: solvent = 95:85:3:100:70. After thorough mixing, the material is extruded into strips and dried at 45°C for 48 hours to obtain cylindrical granular slow-release material A.

[0075] The mass fraction of sulfur in the controlled-release material A in this example was determined to be 5.94 wt%, therefore the sodium persulfate loading in controlled-release material A can be calculated to be 22.09 wt%. The controlled-release performance test results of this example are as follows: Figure 1As shown, the release of the active substance can be divided into two stages: the first stage, from day 0 to 14, is the decomposition and release stage of the outer shell, characterized by a rapid change in release rate and a steep release curve; the second stage, from day 15 to 135, is the slow-release stage of the inner core, characterized by a stable release rate and a smooth curve. The relay release of the first and second stages achieves a multi-stage slow-release effect. The final test results show that the release period of slow-release material A is 135 days. The cumulative release rate of sodium persulfate during the release period is 97.9 wt%, with an average release rate of 1.7 mg / (gd). Throughout the entire slow-release period, no organic matter was detected in the water, and the slow-release material particles remained intact and did not disintegrate.

[0076] Meanwhile, the inventors replaced the first and second starches in this example with ordinary corn starch as raw materials and conducted parallel comparative experiments to prepare sustained-release material DA. The mass fraction of sulfur in sustained-release material DA was determined to be 4.69 wt%, thus the sodium persulfate loading in sustained-release material A was calculated to be 17.51 ​​wt%. The release period of sustained-release material DA was 80 days. The cumulative release rate of sodium persulfate during the release period was 96 wt%, with an average release rate of 2.2 mg / (gd). Comparing the test results of sustained-release material A and sustained-release material DA, it is evident that using modified porous starch as raw material further extends the release period of the agent and results in a more stable release rate.

[0077] Example 2

[0078] (1) The preparation method of modified porous starch is as follows:

[0079] Preparation of porous starch: Potato starch was added to water and stirred until homogeneous to prepare a 15 wt% starch suspension with a pH of 4.5. The suspension was preheated in a water bath at 25°C for 20 minutes. Then, a mixture of α-amylase and saccharifying enzyme at a mass ratio of 1:3.5 was added to the starch suspension, with the total amount of α-amylase and saccharifying enzyme being 0.07‰ of the suspension mass. The suspension was kept at a constant temperature of 35°C in a water bath for 33 minutes. After filtration to remove water, the mixture was dried in a 55°C oven for 20 hours to obtain porous starch. The median pore size of the porous starch was 4.5 μm.

[0080] Preparation of modified porous starch: Using the porous starch prepared above as raw material, water was added to make a 25 wt% starch emulsion. Octenyl succinic anhydride was added, with a mass ratio of octenyl succinic anhydride to porous starch in the starch emulsion of 1:30. The reaction was maintained at a constant temperature of 50℃ in a water bath for 3 hours, and the pH of the reaction solution was controlled at 10.5. Then, hydrochloric acid was added to adjust the pH to 6 to end the reaction. The reaction product was washed, filtered, and dried at 55℃ for 10 hours to obtain modified porous starch.

[0081] In this example, both the first and second starches are modified porous starches as described above.

[0082] 5g of starch was added to 100g of water and stirred thoroughly to form an emulsion. Then, 35g of potassium persulfate was added to the emulsion and dissolved and mixed. After stirring evenly, 30g of 40-mesh wood-based activated carbon (with macropores accounting for 7.8% of the total pore volume) was added to the mixture. The mixture was then stirred thoroughly in a magnetic stirrer for 1 hour. Then, while stirring, 1g of sodium alginate was added to form a colloid. The colloid was placed in a shaker and shaken for 30 minutes to ensure that the starch containing active substances was fully loaded into the activated carbon. The adsorbed activated carbon was then filtered, washed, and air-dried at 25°C for 24 hours to obtain product I, i.e., the activated carbon composite material.

[0083] (2) Weigh some of the above-mentioned modified starch again as the second starch, and calcium persulfate. Mix the starch and calcium persulfate in water to obtain product II. The mass ratio of the feed is water:starch:calcium persulfate = 100:20:50.

[0084] (3) Mix product I obtained in step (1), product II obtained in step (2), strength agent, matrix, and solvent, and then mold and dry to obtain a sustained-release material. The specific steps are as follows:

[0085] (31) Mix the matrix polytetrafluoroethylene powder with a solvent (dichloromethane and n-hexane in a volume ratio of 1:0.5);

[0086] (32) The mixture obtained in step (31) is mixed evenly with product I;

[0087] (33) The mixture obtained in step (32), product II, and the strength agent quartz sand are thoroughly mixed. The product I: product II: quartz sand: polytetrafluoroethylene: solvent = 80:75:1:100:50. After thorough mixing, the material is extruded into strips and dried at 40°C for 60 hours to obtain cylindrical granular slow-release material B.

[0088] The mass fraction of sulfur in the controlled-release material B in this example was determined to be 5.38 wt%. Therefore, the calculated loading of the active substances (potassium persulfate and calcium persulfate) in controlled-release material B is 20.58 wt%. The controlled-release performance test results of this example are as follows: Figure 2As shown, the release of the active substance can be divided into two stages: the first stage, from day 0 to 7, is the decomposition and release stage of the outer shell, characterized by a rapid change in release rate and a steep release curve; the second stage, from day 8 to 132, is the slow-release stage of the inner core, characterized by a stable release rate and a smooth curve. The relay release of the first and second stages achieves a layered, multi-stage slow-release effect. The final test results show that the release period of slow-release material B is 132 days. The cumulative release rate of sodium persulfate during the release period is 95.9 wt%, with an average release rate of 1.73 mg / (gd). Throughout the entire slow-release period, no organic matter was detected in the water, and the slow-release material particles remained intact and did not disintegrate.

[0089] Example 3

[0090] (1) The preparation method of modified porous starch is as follows:

[0091] Preparation of porous starch: Cassava starch was added to water and stirred until homogeneous to prepare a 25 wt% starch suspension with a pH of 6.5. The suspension was preheated in a water bath at 28°C for 25 minutes. Then, a mixture of α-amylase and saccharifying enzyme at a mass ratio of 1:4.5 was added to the starch suspension, with the total amount of α-amylase and saccharifying enzyme being 0.03‰ of the suspension mass. The suspension was kept at a constant temperature of 30°C in a water bath for 35 minutes. After filtration to remove water, the mixture was dried in a 50°C oven for 24 hours to obtain porous starch. The median pore size of the porous starch was 5.5 μm.

[0092] Preparation of modified porous starch: Using the porous starch prepared above as raw material, water was added to make a 35 wt% starch emulsion. Octenyl succinic anhydride was added, with a mass ratio of octenyl succinic anhydride to porous starch in the starch emulsion of 1:45. The reaction was maintained at a constant temperature of 40℃ in a water bath for 3 hours, and the pH of the reaction solution was controlled at 8.5. Then, hydrochloric acid was added to adjust the pH to 6 to end the reaction. The reaction product was washed, filtered, and dried at 45℃ for 16 hours to obtain modified porous starch.

[0093] In this example, both the first and second starches are modified porous starches as described above.

[0094] 10g of starch was added to 100g of water and stirred thoroughly to form an emulsion. Then, 40g of ferrous sulfate was added to the emulsion and dissolved and mixed. After stirring evenly, 40g of 50-mesh wood-based activated carbon (with macropores accounting for 6.7% of the total pore volume) was added to the mixture. The mixture was then stirred thoroughly in a magnetic stirrer for 1.5 hours. Then, while stirring, 2g of sodium alginate was added to form a colloid. The colloid was placed in a shaker and shaken for 50 minutes to ensure that the starch containing active substances was fully loaded into the activated carbon. The adsorbed activated carbon was then filtered, washed, and air-dried at 25°C for 48 hours to obtain product I, i.e., the activated carbon composite material.

[0095] (2) Re-weigh some of the above-mentioned modified starch as the second starch, and ferrous sulfate. Mix the starch and ferrous sulfate in water to obtain product II. The mass ratio of the feed is water:starch:ferrous sulfate = 100:25:55.

[0096] (3) Mix product I obtained in step (1), product II obtained in step (2), strength agent, matrix, and solvent, and then mold and dry to obtain a sustained-release material. The specific steps are as follows:

[0097] (31) Mix the matrix polytetrafluoroethylene powder with a solvent (dichloromethane and n-hexane in a volume ratio of 1:0.8);

[0098] (32) The mixture obtained in step (31) is mixed evenly with product I;

[0099] (33) The mixture obtained in step (32), product II, and the strength agent quartz sand are thoroughly mixed. The product I: product II: quartz sand: polytetrafluoroethylene: solvent = 85:80:2:100:60. After thorough mixing, the material is extruded into strips and dried at 45°C for 60 hours to obtain cylindrical granular slow-release material C.

[0100] The determination showed that the mass fraction of iron in the controlled-release material C was 8.6 wt%, therefore the calculated ferrous sulfate loading in controlled-release material C was 23.34 wt%. The controlled-release performance test results of this controlled-release material are as follows: Figure 3 As shown, the release of the active substance can be divided into two stages: the first stage, from day 0 to 12, is the decomposition and release stage of the outer shell, characterized by a rapid change in release rate and a steep release curve; the second stage, from day 13 to 130, is the slow-release stage of the inner core, characterized by a stable release rate and a smooth curve. The relay release of the first and second stages achieves a layered, multi-stage slow-release effect. The final test results show that the release period of the slow-release material C is 130 days. The cumulative release rate of sodium persulfate during the release period is 96.5 wt%, with an average release rate of 1.73 mg / (gd). Throughout the entire slow-release period, no organic matter was detected in the water, and the slow-release material particles remained intact and did not disintegrate.

[0101] Example 4

[0102] The difference from Example 1 is that the active substance in steps (1) and (2) is glucose, while the rest is the same as in Example 1.

[0103] The glucose loading in the sustained-release material D in this example was determined to be 28.42 wt%. The sustained-release performance test results of this sustained-release material are similar. Figure 1In this example, the release of the active substance can be divided into two stages: the first stage, from day 0 to day 6, is the decomposition and release stage of the outer shell, characterized by a rapid change in release rate and a steep release curve; the second stage, from day 7 to day 132, is the slow-release stage of the inner core, characterized by a stable release rate and a smooth curve. The relay release of the first and second stages achieves a layered, multi-stage slow-release effect. The final test results show that the release period of the slow-release material D is 132 days. The cumulative release rate of sodium persulfate during the release period is 95 wt%, with an average release rate of 1.75 mg / (gd). Throughout the entire slow-release period, no organic matter was detected in the water, and the slow-release material particles remained intact and did not disintegrate.

[0104] Comparative Example 1

[0105] The difference between this example and Example 1 is that the active substance, sodium persulfate, is not added in steps, but all at once. That is, all the materials from steps (1) and (2) of Example 1 are added at once in step (1) of Example 1. The amount of materials added and other operating steps are the same as in Example 1.

[0106] The sustained-release performance test results of the sustained-release material in this example are as follows: Figure 4 As shown, the results indicate that the release period of the slow-release material is only 9 days, which does not achieve the effect of slow release.

[0107] Application examples

[0108] The principle of using slow-release materials to remediate contaminated groundwater is as follows: Figure 5 As shown, the slow-release material A from Example 1 of this invention was used as filler material and filled into a permeable reactive wall. The permeable reactive wall was then placed in the flow path of organically contaminated groundwater. The contaminated groundwater permeated through the wall, and the organic pollutants were oxidized and degraded by the active substances released by the slow-release material, thus removing the pollutants. The pollution removal rate could be calculated by testing the pollutant concentrations in the groundwater upstream and downstream of the permeable reactive wall. In this application example, groundwater contaminated with petroleum hydrocarbons (TPH) was selected, with an influent TPH concentration of (120±5) mg / L. The wall dimensions were set at 10m*0.6m*5.8m, and 1.9 tons of slow-release material were filled at one time as the wall filler material. A pollution remediation application was carried out for 145 days. During this period, the TPH concentrations in the groundwater upstream and downstream of the permeable reactive wall were measured at regular intervals, and the pollution removal rate was calculated. The pollution remediation effect is as follows: Figure 6 As shown, the TPH removal rate remained above 90 wt% during days 0 to 135, reaching a maximum of 97 wt%. After day 135, most of the oxidant in the slow-release material had been released, and the pollution removal rate decreased. This result indicates that the slow-release material has stable slow-release performance and can be continuously released during the slow-release period, successfully remediating contaminated groundwater.

Claims

1. A method for preparing a sustained-release material, characterized in that, The method includes: (1) Disperse the first starch in water, then add the first active substance, activated carbon, and sodium alginate and mix evenly to obtain product I; (2) Disperse the second starch in water, then add the second active substance and mix well to obtain product II; (3) Mix product I obtained in step (1), product II obtained in step (2), strength agent, matrix and solvent, mold and dry to obtain sustained-release material; The first starch in step (1) and the second starch in step (2) are modified porous starches; The method for preparing the modified porous starch includes: dispersing porous starch in water, adding octenyl succinic anhydride and reacting, filtering to obtain a solid, and drying to obtain modified porous starch; wherein the mass ratio of octenyl succinic anhydride to porous starch is 1:(30~55); the method for preparing the porous starch includes: adding α-amylase and saccharifying enzyme to a starch-water suspension, reacting, filtering to obtain a filter residue, and drying to obtain porous starch; In step (1), the first active substance includes one or more of sodium persulfate, potassium persulfate, and ammonium persulfate; In step (1), the following feeding ratio is adopted for each material, namely, the mass ratio of water, sodium alginate, first starch, first active substance and activated carbon is 100: (1~3): (5~15): (35~50): (30~45); In step (2), the second active substance includes one or more of sodium persulfate, potassium persulfate, and ammonium persulfate; In step (2), the mass ratio of water, second starch, and second active substance is 100:(20~30):(50~60); In step (3), the mass ratio of product I, product II, strength agent, matrix, and solvent is (80~95):(75~85):(1~3):100:(50~70); In step (3), the strength agent includes at least one of quartz sand and glass fiber; the matrix includes one or more of polytetrafluoroethylene, polystyrene, polyethylene, and polypropylene; and the solvent includes at least one of dichloromethane and n-hexane. In step (3), the mixing method of product I, product II, strength agent, matrix, and solvent includes: (31) Mix the matrix with the solvent; (32) The mixture obtained in step (31) is mixed evenly with product I; (33) Mix the mixture obtained in step (32), product II and strength agent evenly.

2. The method according to claim 1, characterized in that, In the method for preparing the modified porous starch, the reaction conditions are: a reaction temperature of 40~55℃; and / or, controlling the pH value of the reaction solution to be 8.5~10.5; and / or, a reaction time of 2~6 h.

3. The method according to claim 1, characterized in that, The porous starch has a median pore size of 4.5~6.5μm.

4. The method according to claim 1, characterized in that, In the method for preparing porous starch, the reaction conditions are: temperature 30~40℃, time 33~35 minutes; And / or, the mass ratio of α-amylase to glucoamylase is 1:(3.5~5.5); And / or, the total amount of α-amylase and glucoamylase added accounts for 0.03‰~0.11‰ of the suspension mass; And / or, the starch content in the suspension is 15wt%~30wt%.

5. A sustained-release material prepared by the method according to any one of claims 1 to 4.

6. The application of a sustained-release material prepared by the method according to any one of claims 1 to 4 in the field of sustained-release materials.

Citation Information

Patent Citations

  • Sustained-release potassium permanganate oxidant for in-situ chemical remediation of groundwater

    CN102491425A

  • Sustained release vulcanizing agent, preparation method thereof, and method of using sustained release vulcanizing agent to remove heavy metals and arsenic from acidic solution

    CN107188361A

  • Controlled-release carbon source material for repairing polluted underground water organisms and preparation method thereof

    CN102491497A

  • Processing method of double-modified puerariae porous starch

    CN107141360A

  • Core-shell structure oxidant sustained-release material and preparation method and application thereof

    CN115637156A